2012
DOI: 10.4081/ijfs.2012.3.35
|View full text |Cite
|
Sign up to set email alerts
|

Occurance of Histamine in Fish Products on Market

Abstract: SUMMARYHistamine fish poisoning is quite common and occur in consequence of microbial decarboxylase whose activity begin early in the post-mortem but are triggered in consequence of abuse in the shelf life of fish products. In this study forty-eight samples of tuna, mackerel, anchovies, sardines, fresh or processed were sampled from fish shops and supermarkets in the City of Bologna in the period from January to July 2010. Concentration of histamine was assessed using ELISA quantitative test and presence of ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…Critical points such as inadequate frosting/defrosting cycles, incorrect treatment before consumption of the defrosted tuna, and inappropriate packaging or storage conditions at the retail market are, presumably, at the basis of these findings in agreement with those reported by Altieri et al and Ðordević et al [40,41] Furthermore, fraudulent practices in the treatment of raw tuna with red extracts containing nitrates and/or high levels of antioxidants or with carbon monoxide, as reported in the last years [20], may be other causes of the HIM presence. As shown in Table 1, in the fresh, frozen and defrosted fish category, tuna showed the highest HIM concentrations, in accordance with most of the studies reported in the literature [38,[42][43][44], confirming that tuna is more susceptible to HIM development than mackerel, anchovies, and sardines because of its high content of free histidine and its composition and presence of high levels of bacterial flora. As reported in Table 1 for fresh anchovy samples, an HIM content in the range 2.57-559 mg kg −1 was found, with a mean concentration of 19.6 mg kg −1 .…”
Section: Him Levels In Fish Samplessupporting
confidence: 86%
“…Critical points such as inadequate frosting/defrosting cycles, incorrect treatment before consumption of the defrosted tuna, and inappropriate packaging or storage conditions at the retail market are, presumably, at the basis of these findings in agreement with those reported by Altieri et al and Ðordević et al [40,41] Furthermore, fraudulent practices in the treatment of raw tuna with red extracts containing nitrates and/or high levels of antioxidants or with carbon monoxide, as reported in the last years [20], may be other causes of the HIM presence. As shown in Table 1, in the fresh, frozen and defrosted fish category, tuna showed the highest HIM concentrations, in accordance with most of the studies reported in the literature [38,[42][43][44], confirming that tuna is more susceptible to HIM development than mackerel, anchovies, and sardines because of its high content of free histidine and its composition and presence of high levels of bacterial flora. As reported in Table 1 for fresh anchovy samples, an HIM content in the range 2.57-559 mg kg −1 was found, with a mean concentration of 19.6 mg kg −1 .…”
Section: Him Levels In Fish Samplessupporting
confidence: 86%
“…The highest histamine mean value was obtained with P. saltatrix (59.02 ppm), this concentration was higher than that reported in Bulgarian market ranged from 2.51 to 13.51 (ppm) (Bangieva et al, 2020). Regarding T. trachurus species, our results were way lower than that reported in Portuguese markets (480.25 ppm) (Diniz et al, 2021); our results were higher than that reported in Bologna, Italy (10 ppm) (Mancusi et al, 2010).…”
Section: Histamine Level In Fresh Fishcontrasting
confidence: 74%
“…(2013). The presence of hista-mine-producing bacteria on sashimi could also represent a potential toxicological hazard.…”
Section: Discussionmentioning
confidence: 99%